Treinamento e desenvolvimento de pessoas em um organização do agronegócio: um estudo de caso da empresa Marcon Assessoria Agropecuária - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The People Management plays a very influential role within organizations, is responsible for various administrative processes. Within the Brazilian Agribusiness, there are several organizations that are employers of a large portion of skilled manpower in the country. With technological advances in this sector, the administration of Human Resources must receive focus as an important part in the production processes of companies. In this context, this study sought to examine the processes of managing the training and development of people in a local company MARCON Agricultural Advisory, belonging to the branch of agribusiness. Through a semistructured interview those responsible for the Human Resources sector, results regarding the training techniques used in the company, besides being addressed key aspects of recruitment, selection, motivation and retention of employees were obtained. It could be observed from these data that the company is always attentive to the needs of its customers and seeks to train its employees to better service your target audience. Using techniques of internal and external training with a strategic vision, aiming to upgrade its human capital also worrying about the methods of motivation to its employees, not only financial benefits, but with the organizational climate, thus achieving low rates of turnover.
Keywords: Agronegócio; Gestão de pessoas; Treinamento e desenvolvimento; Agribusiness; People management; Training and development; CNPQ::CIENCIAS EXATAS E DA TERRA